(untitled) (Research, Society and Development, 2020)
In the last few years, the search for healthy-looking foods has grown substantially, which has favored the trade in fruit-based foods. The use of native fruits for the development of jelly is a new alternative for consumption, is a way of preserving the fruits since they have high perishability. The objective of this work was to make biribiri jellies with different concentrations of pectin and to characterize the product in terms of physical-chemical, colorimetric and texture characteristics. Ripe fruits were used and jams of the extra type were made. Three formulations were carried out, and these varied the pectin content (0, 0.5 and 1%). The following analyzes were performed: pH, acidity, soluble solids, water activity, color and texture profile. There was no statistical difference between samples for any parameter. The results showed that the jellies showed an average pH, acidity, soluble solids and water activity of 2.85, 1.28, 63.8 and 0.79 respectively, being ideal to provide food security to the product. The means of the color and texture parameters were L * 19.44, a * 5.64, b * 22.29, hardness 1.2N, adhesiveness -0.13, elasticity 0.90 and cohesiveness 0.65N.Thus, the production of biribiri jelly is a technological possibility for the production of an alternative product, in addition to adding value to the fruit and minimizing its loss due to its high perishability.